Fiqh Analysis of the Age Limit for Marriage and Its Implications for Children's Welfare - Muhammad Fajar; Linda Kartika (Indonesian Journal of Islamic Law, 2021)
Child marriage is a phenomenon that still occurs in Indonesia, with various complex social, health and legal implications. This research aims to investigate the views of jurisprudence regarding the age limit for marriage and its impact on children's welfare. Through a study of classical and contemporary fiqh literature, as well as an analysis of Islamic law regarding the minimum age for marriage, this research reveals various perspectives of ulama regarding underage marriage and its implications for the welfare of children. Empirical data from UNICEF and WHO shows the significant negative impact of child marriage on children's physical and mental health, education and economic future. In the context of Islamic law, it is found that a revision of traditional views is necessary to ensure better protection of children's rights. The research results emphasize the importance of a more holistic and contextual approach in the interpretation of Islamic law to prohibit underage marriage and encourage policies that are more protective of children. It is hoped that this research can provide a strong basis for more effective policy advocacy in protecting children's rights in Indonesia.